Influence of alumina and zirconia nanoparticles on mechanical properties and damping of magnesium - Trojanova, Z.; Drozd, Z.; Lukac, P.; Ferkel, H.; Riehemann, W. (Functional Materials, 2004)
Magnesium polycrystals reinforced with 3 % (vol.) ZrO₂ nanoparticles and 3 % (vol.) AI2₂O₃ nanoparticles were deformed in tension at a constant strain rate at temperatures between 20 and 300°C. The yield stress of both materials decreases rapidly with temperature. The flow stress of Mg+AI2₂O₃ is higher than that of Mg+ZrO₂. Ductility of the composite with zirconia is substantially higher. The difference in the deformation behaviour of both composites is very probably caused by difference in bonding between matrix and ceramic nanoparticles. Поликристаллы магния, упрочненные 3% наночастиц ZrO₂ и 3% наночастиц AI₂O₃, были деформированы растяжением при постоянной скорости деформации в температурном интервале 20-300°C. Предел текучести обоих материалов быстро уменьшается с температурой. Напряжение текучести Mg+AI₂O₃ выше, чем у Mg+ZrO₂. Пластичность композита с цирконием существенно выше. Разница в поведении двух композитов при деформации является скорее всего результатом различия в прочности связи между матрицей и керамическими наночастицами. Полікристали магнію, зміцнені 3 % наночастинок ZrO₂ та 3 % наночастинок AI₂O₃, були деформовані розтягом при постійній швидкості деформації у температурному інтервалі 20-300°С. Границя текучості Mg+AI₂O₃ вища, ніж у Mg+ZrO₂. Пластичність композиту з цирконієм значно вища. Різниця в поведінці обох композитів при деформації є, найімовірніше, наслідком різниці міцності зв’язування матриці з керамічними наночастинками.